PENERAPAN METODE MAMDANI UNTUK SISTEM PENDUKUNG KEPUTUSAN PENENTUAN GOLONGAN OBAT SESUAI DENGAN PENYAKIT DIABETES - Jasri Jasri; Rabby Nazli (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2018)
Erupted diabetes is one of the diseases that cause many deaths. Drug Information Services (PIO) that develop in the modern world. So the IT department can help pharmacists for the health department. Pressure blood glucose levels 70 to 300 millimeters (mmHG). Fuzzy Inference System with mamdani method to determine the appropriate class of drugs by applying fuzzy variables to the occurrence of blood glucose pressure remains normal.